2015
DOI: 10.3390/v7102894
|View full text |Cite
|
Sign up to set email alerts
|

Nucleobase but not Sugar Fidelity is Maintained in the Sabin I RNA-Dependent RNA Polymerase

Abstract: The Sabin I poliovirus live, attenuated vaccine strain encodes for four amino acid changes (i.e., D53N, Y73H, K250E, and T362I) in the RNA-dependent RNA polymerase (RdRp). We have previously shown that the T362I substitution leads to a lower fidelity RdRp, and viruses encoding this variant are attenuated in a mouse model of poliovirus. Given these results, it was surprising that the nucleotide incorporation rate and nucleobase fidelity of the Sabin I RdRp is similar to that of wild-type enzyme, although the Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The discovery of multiple poxviruses in bats leads to inquiries about the possibility of coevolution between the host and virus [50]. Bats, whose species have diverged 50 million years ago, include diverse species in the suborders of “megabats” and “microbats,” differing both on the behavioral and molecular levels [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of multiple poxviruses in bats leads to inquiries about the possibility of coevolution between the host and virus [50]. Bats, whose species have diverged 50 million years ago, include diverse species in the suborders of “megabats” and “microbats,” differing both on the behavioral and molecular levels [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…2). Previous kinetics studies had indicated that incorporation of 2Ј-C-Me-AMP occurs with reduced catalytic efficiency (33), as evidenced by a decreased second-order rate constant k pol /K d,app , where k pol is the maximum polymerase rate constant and K d,app is the apparent dissociation constant for the incoming NTP (Fig. 2).…”
Section: Nmr Studies Of 2-c-methylated Nucleotidementioning
confidence: 93%
“…under the time necessary for the NMR experiments). D, the secondorder rate constants for single-nucleotide incorporation based on the ssAU RNA as determined previously (33,51). The kinetic parameters k pol and K d are the maximum polymerase rate constant and the apparent dissociation constant for the incoming NTP, respectively.…”
Section: C-met Probes Report On Ligand Binding and Conformational Changes Throughout The Rdrp Structurementioning
confidence: 99%
“…in the absence of other Sabin I mutations) also leads to some attenuation of the encoding PV strain (18). In the presence of other Sabin I substitutions, these effects are largely mitigated (46). Nonetheless, the T362I variant can serve as an important tool in understanding how the conformational dynamics of motif D are (un)related to the realignment of the triphosphate.…”
Section: Metal and Solvent Effects Help To Gauge The Effects Of Amino Acid Substitutions On The Prechemistry Conformational Change And Chmentioning
confidence: 99%